Checklist, functional traits, and conservation status of the Ichthyofauna of rivers in Hu’u District, Sumbawa, Indonesia - KARIZMA FAHLEVY; AGUSTINUS SEMBIRING; RIAS KAESSARI MAGENTA; ADI SUROSO; CHARLES P. H. SIMANJUNTAK; ARIES ASRIANSYAH; NURUL WAHIDAH Q. MANIK (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Fahlevy K, Sembiring A, Magenta RK, Suroso A, Simanjuntak CPH, Asriansyah A, Manik NWQ. 2026. Checklist, functional traits, and conservation status of the Ichthyofauna of rivers in Hu’u District, Sumbawa, Indonesia. Biodiversitas 27 (4): d270404. https://doi.org/10.13057/biodiv/d270404. The freshwater fish community of Hu’u District, Sumbawa, Indonesia, remains poorly documented, particularly in rivers outside previously surveyed areas. Rapid assessments were conducted across seven rivers (Hu’u, Lakey, Ncangga, Nangadoro, Puma, Onto, and Tenga) during the wet (February 2023) and dry (July 2023) seasons using cast nets and scoop nets, with two to three hours of sampling effort per site. Fish identification followed standard taxonomic keys, and trait data from available literature were used to classify species into functional entities based on four categorical traits: water column position, substrate preference, feeding habit, and migratory behavior. A total of 17 fish species from seven orders and ten families were recorded. 12 functional entities were recorded. Demersal species were more common across all rivers. Fish species occurred roughly equally across all substrate types. Omnivores were most common. Most species were amphidromous or catadromous. According to IUCN, 13 species are Least Concern, three are Data Deficient, and one is Not Evaluated, and none of the species is protected under Indonesian regulation. These findings provide the first integrated account of species occurrence, functional richness, and conservation status for freshwater fish in Hu’u District rivers. The low species richness and limited functional redundancy suggest potential vulnerability of ecosystem functioning, and the results support the monitoring and prioritization of downstream river conservation in the region.